Research into rail side wearing on curves - Povilaitienė, Inesa; Podagėlis, Igoris (Transport, 2003)
Factors influencing rail side wearing in the curves are described in the article. All of them are divided into uncontrolled, partially controlled and controlled. An experiment was carried out on Lithuanian railway line curves. The experiment proceeding conditions and the obtained results are presented. The object of the experimental research is 19 curves. The investigations of dynamic changes in rail wearing and in rail track geometrical parameters on curves were being carried out for one and a half year. The experimental results, associated with the railway gauge influence on rail wearing on curves are analyzed more precisely. Measurement results are described using mathematical dependences. According to the dependences it is possible to estimate the influence of gauge on rail side wearing on curves.First Published Online: 19 Dec 2011